2015
DOI: 10.1007/s10750-015-2558-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Dikerogammarus villosus (Crustacea, Gammaridae) a ‘killer shrimp’ in the River Rhine system?

Abstract: Communities and food web structures of aquatic ecosystems can be strongly affected by the establishment of alien macroinvertebrate species. In many European waters, the invasion of the Ponto-Caspian amphipod Dikerogammarus villosus has led to displacement of other macroinvertebrates. Predation by D. villosus is often assumed to be the key driver of the displacement based on results of laboratory studies, but this has not been verified in the field. Here, we report our investigation of the relevance of D. villo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 58 publications
3
24
0
Order By: Relevance
“…The success of the Ponto‐Caspian amphipod Dikerogammarus villosus (Gammaridae) , one of the 100 worst invasive alien species in Europe (DAISIE ), is at least in part due to its omnivorous feeding strategies. There is some evidence that its success at outcompeting native species may be due to intraguild predation, although the importance of this mechanism in the field is still debated (Koester, Bayer, & Gergs, ; Koester & Gergs, ; MacNeil & Platvoet, ). Arbačiauskas et al.…”
Section: Overview Of Omnivorymentioning
confidence: 99%
See 1 more Smart Citation
“…The success of the Ponto‐Caspian amphipod Dikerogammarus villosus (Gammaridae) , one of the 100 worst invasive alien species in Europe (DAISIE ), is at least in part due to its omnivorous feeding strategies. There is some evidence that its success at outcompeting native species may be due to intraguild predation, although the importance of this mechanism in the field is still debated (Koester, Bayer, & Gergs, ; Koester & Gergs, ; MacNeil & Platvoet, ). Arbačiauskas et al.…”
Section: Overview Of Omnivorymentioning
confidence: 99%
“…In a review of food webs in Mediterranean rivers, Power et al (2013) at least in part due to its omnivorous feeding strategies. There is some evidence that its success at outcompeting native species may be due to intraguild predation, although the importance of this mechanism in the field is still debated (Koester, Bayer, & Gergs, 2016;Koester & Gergs, 2014;MacNeil & Platvoet, 2005). (a) Where the omnivoreconsumer link is much stronger than the consumer-resource link, the indirect positive effect of the omnivore on the resource should outweigh the direct negative effect and a trophic cascade will be observed.…”
Section: Omnivores Make Better Invadersmentioning
confidence: 99%
“…These include rapid growth rates and early sexual maturation. In addition, both taxa exhibit high fecundity which may be up to three times higher than Gammarus pulex, the most widely distributed native amphipod in north-western Europe (Grabowski et al 2007;Bacela et al 2009;Pöckl 2009;Koester et al 2016). Both D. villosus and D. haemobaphes also have strong competitive advantages over native and other established non-native amphipod taxa associated with their opportunistic and flexible omnivorous feeding characteristics (Dick et al 2002;Platvoet et al 2009a;Rewicz et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This species is often regarded as an omnivore with a strong tendency to predation on macroinvertebrates (Dick & Platvoet, 2000;Dick et al, 2002;MacNeil & Platvoet, 2005). On the other hand, some field studies demonstrated its low trophic position, with a large share of plant food in its diet (Hellmann et al, 2015;Koester et al, 2016). Thus, the feeding habits of D. villosus clearly depend on a number of factors, such as the community structure (Hellmann et al, 2015) or temperature (van der Velde et al, 2009).…”
Section: Discussionmentioning
confidence: 99%